Clinical Characteristics and Outcomes of Neonatal Sepsis due to Pseudomonas putida in South Kalimantan - Andayani, Pudji; Hartoyo, Edi; Pasaribu, Munawaroh; Marhaeni, Wulandewi; Yunanto, Ari; Putra, Nataniel Hadi; Himawan, Gratianus Billy; Salim, Monica Anggriana; Halim, Pricilia Gunawan (Jurnal Kedokteran Brawijaya, 2026)
Pseudomonas putida is a Gram-negative bacterium that can cause nosocomial infections, particularly in neonates. This study aimed to identify the characteristics of neonates with P. putida infection, the antibiotics administered, and the treatment outcomes during a P. putida outbreak. This descriptive study collected data from the medical records of neonates diagnosed with neonatal sepsis admitted to Ulin Hospital, Banjarmasin, between August and October 2022. Data collected included patient characteristics, clinical profiles, laboratory results, antibiotic therapy, P. putida antibiotic sensitivity results, and bacterial culture results from samples taken in the NICU during the outbreak period. Fourteen neonates (6.5%) had positive P. putida during the outbreak of blood cultures, including 13 neonates born at Ulin Hospital and one referred from another health facility. Neonates with P. putida infection exhibited leukopenia, thrombocytopenia, and elevated CRP levels. After obtaining the culture results and antibiotic sensitivity tests, the choice of antibiotics was adjusted based on the bacteria's sensitivity. The antibiotics found compelling during treatment included ciprofloxacin, cefepime, tazobactam, gentamicin, a combination of ciprofloxacin and amikacin, and a combination of piperacillin. Most of the clinical and laboratory characteristics improved following treatment, but three neonates unfortunately died during hospitalization. Overall, there were clinical and laboratory improvements after administering antibiotics according to the culture-based antibiotic resistance results.